Education, Cooperation and Development: The Latin American Situation at the Beginning of the XXI Century - Neira Gómez, Isabel; Portela Maseda, Marta (Education Policy Analysis Archives, 2004)
In this article, we analyze the basic educational needs of the countries of Latin America, the education policies that are evolving within the region, and the policies that are proposed by the developed countries to meet these needs in the future. Educational aid for development will be the focus of this study. The first section contains an analysis of the basic needs in these countries, complemented by an analysis of the policies proposed by international organizations to resolve those needs. Finally, we discuss the influence that education exerts on economic growth and the role placed by international aid to education in the process of development of Latin American countries.